Search
Ask a question
0

(x^3y^-2)^2/(x^5y^3)^-3

simplify and write the resulting expression with only positive exponents

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Philip P. | Effective and Affordable Math TutorEffective and Affordable Math Tutor
4.9 4.9 (384 lesson ratings) (384)
0
(x3y-2)2/(x5y3)-3
 
Remembering that x-a = 1/xa, we can re-write the expression as:
 
(x3)2(x5y3)3/(y2)2
 
Now (xa)b = xab:
 
x6x15y9/y4
 
Since xaxb = xa+b  and xa/xb = xa-b, we can combine terms with the same base and simplify:
 
x6+15y9-4
 
x21y5